Cross-validation of the ego dissolution scale: implications for studying psychedelics - Lynn, Steven Jay; McDonald, Charlie W.; Sleight, Fiona G.; Mattson, Richard E. (Frontiers in Neuroscience, 2023)
Introduction: Ego dissolution, variously called ego loss, self-loss, and ego disintegration, is a hallmark of psychedelic drug use. We cross-validated the 10-item Ego Dissolution Scale (Sleight et al., 2023), which we developed to assess ego dissolution in everyday life, and we included comparator variables that expanded our original assessment of construct validity. Methods: Undergraduate college student volunteers (N = 527) completed the measures online. Results: We replicated the original two factor structure (i.e., subfactors: Ego-Loss and Unity/connectedness with others, the world, universe), and we determined that the total score (Cronbach’s α = .79) and subfactors (Ego-Loss = 78; Unity = .83) possessed adequate-to-good reliability and strong convergent validity (e.g., mindfulness, hallucination-predisposition, sleep variables, personality variables, positive/negative affect transliminality, dissociation/depersonalization), while neuroticism, social desirability did not correlate highly with ego dissolution. We identified distinct patterns of relations of measures associated with the Ego-Loss vs. Unity subfactors. Discussion: We discuss the implications of the use of the EDS for studying everyday aspects of ego-dissolution, the long-term effects of psychedelic use, and the value of using the scale in conjunction with measures of the acute effects of psychedelics.